Deskripsi Perbedaan Tingkat Pengetahuan Tentang Alat Pengambilan Keputusan Ber-KB (SKB) Dan ABPK Pada Bidan di Kabupaten Banyumas - Neni Fitriani; Evicenna Naftuchah R (JURNAL BIDANG ILMU KESEHATAN, 2026)
Background: Family planning (FP) services remain suboptimal, as indicated by the low utilization of Long-Acting Reversible Contraceptives (LARCs) and limited counseling competence among midwives. Insufficient knowledge and counseling skills contribute to the ineffective implementation of FP counseling. Objective: To compare the knowledge levels of midwives regarding the Balanced Counseling Strategy (BCS) and the Decision-Making Tool for Family Planning (DMT-FP) in Banyumas Regency. Methods: A quantitative descriptive study was conducted among 75 midwives selected through purposive sampling. Data were collected using a knowledge questionnaire and analyzed descriptively. Results: Most respondents were aged 31–40 years (42.7%) with 11–20 years of work experience (50.7%). Good knowledge of DMT-FP was found in 85.3% of respondents, compared with only 2.7% for BCS. The mean knowledge score was higher for DMT-FP (2.85 ± 0.36) than for BCS (1.69 ± 0.52). Conclusion: Midwives demonstrated significantly better knowledge of the Decision-Making Tool for Family Planning than the Balanced Counseling Strategy, indicating the need to strengthen training on BCS implementation.